The Role Of Digital Competence And Work Motivation On Teacher Performance In The Era Of Digitalization Of Junior High Schools In Cirebon City - Hesti Hesti; Noveria Susijawati (LPPM of NAROTAMA UNIVERSITY, 2026)
Objective: This study aims to analyse the influence of digital competence and work motivation on teacher performance in public junior high schools in Cirebon City in the era of educational digitalisation. Design/methodology/approach: This study used a quantitative approach with an associative research design. The sample consisted of 90 teachers selected using purposive sampling. Data were collected through a Likert scale questionnaire and analysed using multiple linear regression with SPSS. Findings: The results show that digital competence has a positive and significant effect on teacher performance (B = 0.102; t = 4.125; p < 0.05). Work motivation also has a positive and significant effect on teacher performance (B = 0.619; t = 13.432; p < 0.05). Concurrently, digital competence and work motivation significantly influence teacher performance (F = 130.055; p < 0.05). This model explains 74.9% of the variation in teacher performance (Adjusted R² = 0.749). Research limitations/implications: This study only focused on public junior high school teachers in Cirebon City, so the findings may not fully represent teachers in other regions. Practical implications: The results of this study provide insights for schools and education authorities in designing programmes to improve digital competence and strengthen teacher motivation in order to improve teacher performance. Originality/value: This study provides empirical evidence on the role of digital competence and work motivation in improving teacher performance in the context of school digital transformation. Article type: Research article